2011
DOI: 10.1152/japplphysiol.00220.2011
|View full text |Cite
|
Sign up to set email alerts
|

Elevated vertebrobasilar artery resistance in neonatal spontaneously hypertensive rats

Abstract: There is a strong correlation between increased vertebral artery resistance and arterial blood pressure in humans. The reasons for this increased resistance at high systemic pressure remain unknown, but may include raised sympathetic activity. With the recent finding that prehypertensive spontaneously hypertensive (PHSH) rats, which have raised sympathetic nerve activity, but a blood pressure comparable to normotensive rat strains, we hypothesized that its vertebrobasilar vascular resistance would already be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
67
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 43 publications
5
67
0
2
Order By: Relevance
“…It should be noted that, in addition to the autonomic-immune drive, increased arterial pressure in the SHR is maintained by hypertrophy of peripheral arteries/arterioles (1). Differently from the ANG II-induced hypertension model, which is mostly related to neurogenic drive, SHR exhibits both early autonomic dysfunction (34) and vascular remodeling (3,8). These findings explain the conflicting data: normalization of arterial pressure in ANG II-induced hypertension (7,13,18) and hypertension attenuation in the SHR after chronic blockade of hypothalamic inflammation (14).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, in addition to the autonomic-immune drive, increased arterial pressure in the SHR is maintained by hypertrophy of peripheral arteries/arterioles (1). Differently from the ANG II-induced hypertension model, which is mostly related to neurogenic drive, SHR exhibits both early autonomic dysfunction (34) and vascular remodeling (3,8). These findings explain the conflicting data: normalization of arterial pressure in ANG II-induced hypertension (7,13,18) and hypertension attenuation in the SHR after chronic blockade of hypothalamic inflammation (14).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that SHRs display increased vertebrobasilar artery remodeling and constriction (Cates et al . 2011), which may explain, at least in part, why the post‐stimulus overshoot in SHRs is maintained at a similar level before ganglionic blockade, despite operating at a hypoxic baseline level. Alternatively, it may be possible that SHRs have greater capacity to increase post‐stimulus brainstem oxygenation because they are hypoxic at rest or because they have slower O 2 consumption rates.…”
Section: Discussionmentioning
confidence: 99%
“…142 Intriguingly, narrower lumens and thicker vessel walls are observed in the vertebral and basilar arteries of the pre-hypertensive SHR compared with normotensive rats. 16,143 Similarly, in humans with hypertension, the vertebral arteries also appear to be narrowed and thickened and their vascular resistance is highly correlated with arterial pressure levels. 138 It has been proposed that triggering of SNA and systemic hypertension in response to inadequate cerebral blood flow is a protective mechanism to maintain perfusion.…”
Section: Drug-resistant Hypertension-how To Treat?mentioning
confidence: 99%
“…138 It has been proposed that triggering of SNA and systemic hypertension in response to inadequate cerebral blood flow is a protective mechanism to maintain perfusion. 16,46,143,144 This warrants further exploration as a potential mediator of human hypertension.…”
Section: Drug-resistant Hypertension-how To Treat?mentioning
confidence: 99%